2019
DOI: 10.1002/admt.201800594
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performances Flexible Temperature Sensor Composed of Polyethyleneimine/Reduced Graphene Oxide Bilayer for Real‐Time Monitoring

Abstract: sensor with enough sensitivity, accuracy, and durability which can realize real-time and long-term temperature monitoring is strongly desired.To date, some researches on skinattachable temperature sensors were reported, in which different kinds of materials, including metal nanoparticles/ nanowires, [4,5] graphene, [6][7][8][9][10] carbon nanotubes (CNTs), [11][12][13] polymers (such as poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS)), [5a,10,12,14] and others, have been explored as temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 42 publications
2
81
0
1
Order By: Relevance
“…For instance, continuous monitoring of the skin temperature in real time is important in predicting the cognitive status of the human body and thermal environments, as well as the early diagnosis of diseases. [ 5 ] Simultaneously, high stain sensitivity is a prerequisite for the accurate measurement of subtle human‐body‐induced deformations such as pulses and heartbeats to substantial deformations induced by joint motions. [ 6 ] In general, to meet the requirements of a multifunctional sensor for e‐skin, the sensitivity, stretchability, and acquisition of multiple stimuli without crosstalk are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, continuous monitoring of the skin temperature in real time is important in predicting the cognitive status of the human body and thermal environments, as well as the early diagnosis of diseases. [ 5 ] Simultaneously, high stain sensitivity is a prerequisite for the accurate measurement of subtle human‐body‐induced deformations such as pulses and heartbeats to substantial deformations induced by joint motions. [ 6 ] In general, to meet the requirements of a multifunctional sensor for e‐skin, the sensitivity, stretchability, and acquisition of multiple stimuli without crosstalk are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…Such sensors using resistance temperature detectors generally employ metallic conductors such as platinum (Pt), [2] silver nanowires (AgNWs), [12] silver nanoparticles (AgNPs), [3] and graphene nanoplatelets (GNPs) on a flexible substrate. To date, different kinds of materials such as graphene and its derivatives (e.g., rGO and graphite) composited with PEDOT:PSS, [13,14] carbon nanotubes (CNTs), and cationic polymer (PEI) [5] have been explored for use in thermoresistive temperature sensors. The electrical and thermal properties of graphene oxide (GO) or even reduced graphene oxide (rGO) are different from those of pristine graphene because of structural defects or functional groups (e.g., COOH) or sometimes sp 3 -carbons do not convert to sp 2carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of temperature transducing materials such as ultrathin metal elements, carbon nanotubes (CNTs), Si nanoribbons, conductive polymers, graphene, Ag nanocrystal, gels, and their composites have been developed to fabricate flexible temperature sensors with distinct sensing properties. [ 1–3,7–29 ] Furthermore, it is reported that chemical modification has significant impact on the sensitivity of some temperature sensing materials, such as Ag nanocrystal, poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), hydrogel, etc. [ 16,22–26 ] Among various candidate materials, graphene and its derivatives have emerged as promising candidates for temperature sensing due to their extraordinary electrical and mechanical properties, such as one‐atom thickness, thermal and electrical conductivity, strong sensitivity to sample size, mechanical flexibility, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in flexible and wearable electronics has enhanced the possibility of continuous healthcare monitoring in daily life through the development of many kinds of wearable, conformable sensors [1][2][3][4][5][6][7][8][9][10] . These sensors mainly include flexible temperature sensors [11][12][13][14][15][16] , pressure/force sensors [17][18][19][20][21][22][23][24][25] , humidity sensors [26][27][28][29] , ultrasonic sensors 30,31 , optical sensors [32][33][34] , and biochemical sensors, but most are created to achieve noninvasive detection for a single vital indicator, such as body temperature (BT), heart rate (HR)/arterial pulse, blood pressure (BP), respiratory waves (RWs), or jugular venous pulse. To identify or diagnose human body states, multiple different vital indicators should be monitored continuously.…”
Section: Introductionmentioning
confidence: 99%